Analytical model on progressive collapse resistance of prestressed precast concrete frame under middle column removal scenario. Issue 7 (May 2022) - Li, Zhong-Xian; Liu, Haokun; Shi, Yanchao; Ding, Yang; Cui, Jian
This paper investigates an analytical model on progressive collapse resistance of prestressed precast concrete (PC) frame structures. The analytical model is established based on a sub-frame with two stories and two spans under middle column removal scenario, in which the vertical resistance of two-span beam in each story is obtained according to force equilibrium and deformation compatibility of the beam. The tension-stiffening effect and bond slip of top bars near side joint interface are considered in the model to predict the collapse resistance of the beam at compressive arch action (CAA) stage and tensile catenary action (TCA) stage accurately. Besides, to consider the distinct mechanical behavior of beams in failed span in different stories in the process of progressive collapse, the model is related to the restrained stiffness of beam ends, which is determined according to deformation compatibility and force equilibrium of side column in frame. The accuracy of the analytical model is verified according to the results of tests and numerical simulation. Parametric studies are conducted based on the proposed analytical model to investigate the effects of structural parameters and boundary conditions on vertical resistance of the two-span beam in the failed span. The results show that increasing the length of dissipated segment of top bars can improve the structural ductility in progressive collapse, and increase the TCA capacity. Increasing the initial tension of steel strands can enhance the CAA capacity, but the effect of enhancement is alleviated with the increase of initial tension. The larger restrained stiffness can increase the CAA capacity of beam, and the translation stiffness has a more prompt effect on the vertical resistance of beam than the rotation stiffness.